Radial water intakes as a tool for enhancing the resilience of water supply systems in Ukraine - Kravchuk, Oleksandr; Kravchuk, Andriy; Voznyi, Oleksandr (European Open Science Space, 2026)
The article examines radial water intakes as a resilient alternative to traditional surface water supply systems in Ukraine under wartime threats and post-war recovery. Owing to bank filtration, deep underground placement, and compact design, these facilities provide protection against pollution, reservoir shallowing, and military damage while ensuring energy autonomy and operational stability. Their long service life and economic efficiency make them a strategic solution for rebuilding critical water infrastructure in line with the “Build Back Better” principle.